Transforming Inheritance Law in the Digital Era: Challenges, Opportunities, and Adaptive Strategies for Indonesia - Tendri Hardiyansyah; Benyy Djaja; Maman Sudirman (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The Fourth Industrial Revolution and Society 5.0 have introduced significant challenges to inheritance law in Indonesia, particularly with the emergence of digital assets that reshape concepts of ownership and inheritance. This research aims to explore the transformation of inheritance law in the digital era, identify challenges and opportunities, and formulate adaptive strategies. The study employs a qualitative approach with a normative and empirical juridical design, involving literature review, in-depth interviews, and focus group discussions. The findings reveal regulatory gaps in accommodating the inheritance of digital assets, complexities arising from the pluralism in inheritance law, and technical and security challenges in digital inheritance. On the other hand, blockchain technology and smart contracts present innovative opportunities. This research recommends a comprehensive revision of the existing legal framework, harmonization of legal pluralism, the adoption of technology within the inheritance system, enhanced digital literacy, and international cooperation to address cross-border issues. In conclusion, transforming inheritance law in the digital era requires a multidisciplinary approach that integrates legal, technological, and socio-cultural aspects to create a system that is adaptive yet grounded in Indonesia's local wisdom.